Differences in brain structure and function in children with the FTO obesity‐risk allele - Claudia Lugo‐Candelas; Yajing Pang; Seonjoo Lee; Jiook Cha; Susie Hong; Lisa Ranzenhofer; Rachel Korn; Haley Davis; Hailey McInerny; Janet Schebendach; Wendy K. Chung; Rudolph L. Leibel; et al. (Wiley, 2020)
Summary Objective Noncoding alleles of the fat mass and obesity‐associated (FTO) gene have been associated with obesity risk, yet the underlying mechanisms remain unknown. Risk allele carriers show alterations in brain structure and function, but previous studies have not disassociated the effects of genotype from those of body mass index (BMI). Methods Differences in brain structure and function were examined in children without obesity grouped by their number of copies (0,1,2) of the FTO obesity‐risk single‐nucleotide polymorphism (SNP) rs1421085. One hundred five 5‐ to 10‐year‐olds (5th-95th percentile body fat) were eligible to participate. Usable scans were obtained from 93 participants (15 CC [homozygous risk], 31 CT [heterozygous] and 47 TT [homozygous low risk]). Results Homozygous C allele carriers (CCs) showed greater grey matter volume in the cerebellum and temporal fusiform gyrus. CCs also demonstrated increased bilateral cerebellar white matter fibre density and increased resting‐state functional connectivity between the bilateral cerebellum and regions in the frontotemporal cortices. Conclusions This is the first study to examine brain structure and function related to FTO alleles in young children not yet manifesting obesity. This study lends support to the notion that the cerebellum may be involved in FTO‐related risk for obesity, yet replication and further longitudinal study are required.